Postpartum multivessel spontaneous coronary artery dissection confirmed by coronary CT angiography - Schroder, Catherine (Baylor Health Care System, 2006)
Spontaneous coronary artery dissection is a rare but potentially life-threatening event associated with the peripartum period. We present a case of postpartum multivessel spontaneous coronary artery dissection diagnosed by conventional angiography and monitored with computed tomographic coronary angiography. The patient was initially managed medically and later received a coronary stent.